Coming 2 America [compact disc] : Amazon original motion picture soundtrack. - YG, 1990-; Megan Thee Stallion, 1995-; Legend, John; Burna Boy (Musician); Rodgers, Nile; Taylor, Teyana, 1990-; Fowler, Jermaine; Big Sean, 1988-; Ice-T (Musician); Davido; Knight, Gladys, 1944- (Def Jam, 2021)
The soundtrack creates a new era for Coming to America fans with three new tracks from YG feat. Big Sean; Bobby Sessions feat. Megan Thee Stallion; and John Legend and Burna Boy feat. Nile Rodgers while tapping into nostalgia with classic covers from superstars such as: Teyana Taylor, Tiwa Savage, Public Enemy, and special guests featured in the film.